River water quality in Langat basin, Selangor, Malaysia - Mohamed Abu Yusof; Nordin Hasan; Md.Pauzi Abdullah (Environmental Management Society, Malaysia, 2002)
The Langat Basin is the focus of much recent development. Several mega-projects such as the new federal government administrative capital of Putrajaya, the multimedia super corridor (MSC), Cyberjaya, and the Kuala Lumpur International Airport (KLIA) are located in the Basin. The Langat Basin also become the focus of major hub of manufacturing industries in the Selangor State. The rivers of Langat Basin not only have a significant role in the ecology of the basin, but also contribute substantially to potable, industrial and agricultural water uses in the Basin threaten the quality of its river. The water quality of Langat Basin rivers was monitored for 12 months. Samples were collected monthly from 14 stations along the Langat River and its tributaries. The results were compared to Interim National Water Quality Standards for Malaysia (INWOS) for the support of aquatic life and supply water for potable, industrial, recreation and agricultural water uses. The water Quality Index (WQI) of the Department of Environment (DOE) was used to classify stretches of the river according to it river classification scheme. Analysis result suggest that Langat Basin rivers are polluted by organic matter, sediment, ammonical-nitrogen, phosphate-phosphorous, oil and grease, phenol, iron (Fe), lead (Pb), Copper(Cu) & cadmium(Cd). Parts of the Langat River and Batang Nilai River would be classified as Class IV rivers (very highly polluted) while other parts of the river and its tributaries the Semenyih River, Batang Labu River and Labu would fall as Class III (polluted) and Class II (slightly polluted) rivers. Manufacturing industries, sewage treatment plants, livestock and pig farms, urban area, agricultural land and solid waste dumpsites contributed to river water quality degradation in the Langat Basin. Any further deterioration of the quality of its river water will adversely affect the ability of the rivers to provide vital ecosystem services and support of healthy aquatic life necessary to the health of the Basin’s ecosystem